Unraveling hegemony digital: A framework CDA-semiotic framework for sustainable social epistemic justice - Anam, Mohamad Nurul (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In an increasingly digitized world, religion and culture have transcended their traditional roles. They are now instruments of hegemony that shape—and often destroy—our collective perception of social sustainability. This research examines how digital media platforms, through algorithms and